Teachers' Perceptions of AI Integration in the Learning Process in the Digital Era - Bayu Saputra; Daniel Rinaldi (Jurnal Evaluasi dan Pembelajaran, 2026)
Digital transformation has brought significant changes to education, including the use of artificial intelligence (AI) to enhance learning effectiveness. However, teacher acceptance of AI remains variable, influenced by technological understanding, institutional readiness, and psychological and pedagogical factors. This study aims to analyze teacher perceptions of AI, identify factors influencing its acceptance, and provide recommendations for more inclusive implementation. A mixed methods approach was used, with a Likert- based quantitative survey. Scale and qualitative interviews explored teachers' experiences in adopting AI. This research was conducted in the Mataram Baru District Teachers' Working Group (KKG), with the support of academic partners to facilitate access to respondents and data validation. Analysis included descriptive statistics to identify patterns of AI acceptance and thematic analysis of interviews to understand the challenges and opportunities in integrating this technology. The results showed that teachers have positive perceptions of AI integration in school learning. Teachers considered AI useful in assisting with the development of teaching materials, creating questions, and providing supplementary materials. Meanwhile, factors influencing teacher acceptance and readiness were technical aspects. Perceived barriers included limited technical skills and school infrastructure. Overall, AI acceptance in this study was influenced by interest, individual attitudes, and external factors.